KAJIAN DAYA DUKUNG FISIK WISATA DANAU DI PANTAI PASIR PUTIH PARBABA KABUPATEN SAMOSIR (The Study of Physical Carrying Capacity Lake Tourism at Parbaba Pasir Putih Beach District Samosir) - Nancy Rolina; Pindi Patana; Yoes Soemaryono (AQUACOASTMARINE, 2016)
Parbaba Pasir Putih Beach is one of the tourist area in Lake Toba that have a potential to tourism activity. This study aims to determine physical carrying capacity of the area as a tourist destination. This research was conducted in April-May 2016 at Parbaba Pasir Putih Beach District Samosir. The data used primary and secondary data. The research location was divided into three stations and observed activity are boating, water bikes, sit relax, swimming and banana boat. The results showed that the stations 1, 2 and 3 are very appropriate (S1) for swimming while boating and water bikes are very appropriate (S1) at the station 2. Activities banana boat is very appropriate (S1) at station 3. Tourism suitability index at station 1 for swimming (84.72%). Tourism suitability index at station 2 for boating (83.33%), water bikes (84.31%), and swimming (84.72%). Tourism suitability index at station 3 for swimming (91,66%) and banana boat (85,71%). The physical carrying capacity of area with in 93.315 m2 is 5.366 people per day. The value of the natural beauty of the Parbaba Pasir Putih Beach 94,62% beautiful and the value of the comfort of this area, namely 93,54% are comfortable.Keywords : Beauty, Comfort, IKW, Parbaba Pasir Putih Beach, Physical Carrying Capacity of The Region, Tour